2005
DOI: 10.4141/a05-013
|View full text |Cite
|
Sign up to set email alerts
|

Genetic correlations among indicator traits for carcass composition measured in yearling beef bulls and finished feedlot steers

Abstract: among indicator traits for carcass composition measured in yearling beef bulls and finished feedlot steers. Can. J. Anim. Sci. 85: 463-473. Genetic correlations were examined among 10 live growth and ultrasound traits measured in yearling beef bulls (n = 2172) and four carcass traits measured in crossbred finished feedlot steers (n = 1031). Heritabilities ranged from 0.13 (bull ultrasound longissimus muscle width) to 0.83 (yearling bull hip height). Genetic correlations indicated that selecting yearling bulls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 31 publications
0
14
1
Order By: Relevance
“…When analyzing the genetic correlations between subcutaneous fat and height measured at different body locations, such as hump height or wither Ultrasound and carcass genetic parameters for Nelore height, Aass (1996) and Smith et al (2007) also found moderately negative genetic correlations of −0.29 and −0.20 between these traits, respectively. However, some authors (e.g., Waldner et al, 1992;Bergen et al, 2005) reported that the genetic correlation between HH and BF was close to zero (−0.07 and 0.01, respectively). Therefore, our results suggest that long-term selection for taller animals would tend to produce animals with less subcutaneous fat (i.e., later maturing in terms of carcass finishing).…”
Section: Resultsmentioning
confidence: 94%
“…When analyzing the genetic correlations between subcutaneous fat and height measured at different body locations, such as hump height or wither Ultrasound and carcass genetic parameters for Nelore height, Aass (1996) and Smith et al (2007) also found moderately negative genetic correlations of −0.29 and −0.20 between these traits, respectively. However, some authors (e.g., Waldner et al, 1992;Bergen et al, 2005) reported that the genetic correlation between HH and BF was close to zero (−0.07 and 0.01, respectively). Therefore, our results suggest that long-term selection for taller animals would tend to produce animals with less subcutaneous fat (i.e., later maturing in terms of carcass finishing).…”
Section: Resultsmentioning
confidence: 94%
“…Nevertheless, the Guzerat breed has made a great contribution to Brazilian cattle production, improving productivity, hardiness, precocity and meat quality (Junior et al, 2013). Traits such as rib-eye area, backfat and rump fat thickness, intramuscular fat percentage and visual score for finishing have been continuously assessed in breeding programs because they are related to meat quality, carcass yield and cutability, and organoleptic properties (Bergen et al, 2005;Neto et al, 2009;Junior et al, 2013;Cafe et al, 2018), while other traits such as dry matter intake, average daily gain, metabolic weight, residual feed intake and margin are related to production efficiency (Basarab et al, 2003;. Traditionally, genetic breeding programs in Brazil have only considered traits related to reproduction and adaptability; more recently these programs have included carcass characteristics, mainly in Nellore, with the aim to predict the genetic merit and expected progeny differences (Neto et al, 2009), but Guzerat has remained sidelined in this area.…”
Section: Introductionmentioning
confidence: 99%
“…The longissimus muscle area (LMA) is an efficient indicator of the carcass yield, carcass muscularity [3], carcass weight, fat and muscle traits in steers [4]. The subcutaneous fat covering over the longissimus muscle acts minimizing evaporative weight loss of the carcass in the cooler besides been an efficient carcass-finishing indicative [5].…”
Section: Introductionmentioning
confidence: 99%